2003
DOI: 10.1163/157006803322697416
|View full text |Cite
|
Sign up to set email alerts
|

Sacred Capital: Pierre Bourdieu and the Study of Religion

Abstract: This article offers a critical analysis of Pierre Bourdieu's work and its importance for the study of religion. Analysis and criticim of Bourdieu's theories with reference to the example of the Bˆuls, a loose, eclectic tradition of wandering minstrels and self-proclaimed spiritual "madmen", which has flourished throughout Bengal (northeast India and Bangladesh) since at least the late nineteenth century, was chosen for two reasons: first, because much like Bourdieu, the Bˆuls make frequent use of a "marketplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Bourdieu 1991;Berlinerblau 1999;Collins, 2002;Verter 2003;Rey 2007, Mellor andShilling 2010b; see also Lee, 2010). Despite this, it is common to engage with his writings selectively, sidestepping, for example, his socio-economic reductionist view that religion involves misrecognizing the structure of the social world as the natural-supernatural structure of the cosmos (Bourdieu 1991, 14, 16, 19-22;1977, 129;1987, 124;1991, 16 Csordas 1994), or by questioning his assumptions about the passivity associated with the inculcation of a religious habitus, as well as his broader class-based analysis Martin 2000;Jenkins 2002;Engler 2003;Urban 2003;Lau 2004).…”
Section: Modernity Reflexivity and The Habitusmentioning
confidence: 99%
“…Bourdieu 1991;Berlinerblau 1999;Collins, 2002;Verter 2003;Rey 2007, Mellor andShilling 2010b; see also Lee, 2010). Despite this, it is common to engage with his writings selectively, sidestepping, for example, his socio-economic reductionist view that religion involves misrecognizing the structure of the social world as the natural-supernatural structure of the cosmos (Bourdieu 1991, 14, 16, 19-22;1977, 129;1987, 124;1991, 16 Csordas 1994), or by questioning his assumptions about the passivity associated with the inculcation of a religious habitus, as well as his broader class-based analysis Martin 2000;Jenkins 2002;Engler 2003;Urban 2003;Lau 2004).…”
Section: Modernity Reflexivity and The Habitusmentioning
confidence: 99%
“…In the recent debate between Hugh Urban and Bradford Verter about Bourdieu in the pages of MTSR (Urban 2003, 2005, Verter 2004), Urban raises the question of what an analysis of the field of religious studies modeled after Bourdieu's analysis of fields would look like (2005: 166). Despite the fact that the question is posed for somewhat unfair purposes, it is an important question.…”
Section: The Field Of Religious Studies: Towards a Reflexive Sociologmentioning
confidence: 99%
“…Both Urban (2003) and Verter (2003 and2004) have criticized Bourdieu's relative inattention to the interconnection between various fields, and Verter suggests that Bourdieu treats fields as an archipelago of islands (2003: 162). Bourdieu always suggested that the relation between fields was an "extremely complex" question that he was reticent to try to answer, in part because of his distaste for the rigid schemas of the grand theorists and models that provide answers rather than relevant questions for empirical research.…”
Section: The Field Of Religious Studies: Towards a Reflexive Sociologmentioning
confidence: 99%
See 1 more Smart Citation
“…While the latter may be the case in some circum stances (for example constituted by similar relationships towards different religious fields) not all "modes" of nonreligiosity may necessarily represent a relations that can be observed with quite different tools (for a discussion of "spiritual" and "sacred" capital see Verter 2003;Urban 2003 ). distinct kind.14 The suggestion to focus on different modes of nonreligiosity is inspired by attempts to differentiate between modes of religiosity (see Berner 2004and Quack 2012aand 2012c.…”
mentioning
confidence: 99%